Efektivitas teknik breast care terhadap produksi ASI padab Ibu post partum berbasis teori dorothea orem - Nurul Eka Yoga Miftachurrahmah; Siti Patonah; Sri Mulyani; Evita Muslima Isnanda Putri (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2025)
Background: The postpartum period is an important time for physical and emotional recovery, during which breast care is necessary to help increase milk production. However, many postpartum mothers in the Pungpungan Community Health Center working area are unable to produce milk optimally. Some mothers say that their milk has not flowed smoothly until the third day, causing mastitis and sore nipples due to a lack of breast care. Purpose: To analyze the effectiveness of breast care techniques on breast milk production in postpartum mothers in the Pungpungan Health Center service area. Method: A pre-experimental study design using a one-shot case study design, with total sampling involving 21 respondents. The independent variable was breast care, and the dependent variable was postpartum mothers' breast milk production. Data collection instruments included observation sheets and questionnaires. Data processing utilized editing, coding, scoring, tabulation, and the Friedman test. Results: Of the 21 respondents, it was found that the majority (15 people, 71.4%) had low breast milk production before breast care, while the majority (18 people, 85.7%) had good breast milk production after breast care. The results of the Friedman test showed a p-value (Asymp. Sig 2) of 0.000, indicating that the breast care technique is effective in improving breast milk production in mothers. Conclusion: Breast care techniques are effective in promoting milk production. Postpartum mothers are expected to consistently practice the breast care techniques they have learned in order to increase and facilitate milk production.